Understanding the effect of fluoride on corrosion behavior of pure titanium in different acids. (November 2021) - Li, Xiaoqi; Wang, Liwei; Fan, Lin; Zhong, Mingyuan; Cheng, Lianjun; Cui, Zhongyu
Abstract: Corrosion behavior of pure titanium in H2 SO4, HCl and HNO3 with different concentrations of F - was studied with electrochemical testing and morphology observation. The threshold F - concentration triggering severe corrosion is between 0.0005 and 0.001 M in the three acids. The F - promotes anodic dissolution and inhibits oxygen reduction, resulting in the decrease of cathodic current density. The corrosion process presents a two-step reaction mechanism, and the influence mechanism of fluoride in different acids is different. The oxidizing nitrate participates in the corrosion reaction as an oxidant and accelerates the corrosion, resulting in the most severe corrosion in fluoride-bearing HNO3 . Highlights: Corrosion of pure Ti in fluoride-bearing H2 SO4, HCl and HNO3 was investigated. Critical fluoride concentration is independent of the acid radical ion. More severe corrosion occurs in HNO3 than that in H2 SO4 and HCl. The F - promotes the anodic dissolution and inhibits oxygen reduction. NO- 3 participates in the cathodic reaction as an oxidant and expedites corrosion.